2003
DOI: 10.1182/blood-2003-02-0586
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of donor-specific transfusion tolerance: preemptive induction of clonal T-cell exhaustion via indirect presentation

Abstract: Induction of transplantation tolerance to alloantigens without general immunosuppression remains an enduring challenge. Injecting a donor-specific transfusion (DST) of spleen cells together with blocking ␣CD154 antibody prior to graft transplantation is an effective way to induce long-lived graft acceptance. Using a novel T-cell receptor (TCR) transgenic (Tg) model of CD4 ؉ T-cell-mediated rejection, this study sheds new insights into the cellular basis for enhanced graft survival induced by DST and ␣CD154. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 28 publications
3
89
1
Order By: Relevance
“…ϩ TCR-transgenic mice were provided by Dr. R. Noelle (Dartmouth University Medical School, Lebanon, NH) (27). Both TEa mice and OT II mice were crossed with our foxp3gfp mice.…”
Section: Animalsmentioning
confidence: 99%
“…ϩ TCR-transgenic mice were provided by Dr. R. Noelle (Dartmouth University Medical School, Lebanon, NH) (27). Both TEa mice and OT II mice were crossed with our foxp3gfp mice.…”
Section: Animalsmentioning
confidence: 99%
“…It has been proposed that such treatment impairs the maturation of host antigen-presenting cells, generates tolerogenic dendritic cells, promotes T cell anergy (12) and deletion (13), and induces regulatory T cells (14,15). Graft survival can be further enhanced by donor-specific transfusion (DST) (16), and in the presence of anti-CD154, the infused DST is presented by host antigen-presenting cells in a tolerogenic manner, resulting in T cell anergy and regulation (17). Blocking CD154-CD40 interaction also prevents the T-dependent humoral responses (18).…”
mentioning
confidence: 99%
“…Brouard and Soulillou and colleagues demonstrated that infusion of splenocytes without additional immunosuppression leads to long-term survival of cardiac allografts through expansion of Treg and that transfer of long-term survivor splenic T cells to new allograft recipients transfers long-term allograft survival in an Ag-specific manner (Lair et al, 2007). Importantly, in the Quezada study, the injected living donor splenocytes did not directly interact with CD4 + T cells (Quezada et al, 2003). This finding suggests that living splenocytes upon i.v.…”
Section: Cellular Therapies In Solid Organ Transplantationmentioning
confidence: 53%
“…DST in transplantation of solid organ allografts: Quezada et al (2003) showed that DST significantly prolongs skin allograft survival through peripheral deletion of indirect pathway CD4 + T cells and increased numbers of regulatory T cells (Treg). Brouard and Soulillou and colleagues demonstrated that infusion of splenocytes without additional immunosuppression leads to long-term survival of cardiac allografts through expansion of Treg and that transfer of long-term survivor splenic T cells to new allograft recipients transfers long-term allograft survival in an Ag-specific manner (Lair et al, 2007).…”
Section: Cellular Therapies In Solid Organ Transplantationmentioning
confidence: 99%